Since you've got two expressions for y as a function of x, put them equal to each other and solve for x:
-3/5 x + 7 = 8x
=> -3x + 35 = 40x
=> x = 35/43
Then substitute into one of the original equations to get y:
y = 8x = 8(35/43) = 280/43.
2007-01-14 12:53:40
·
answer #1
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
Before I begin my answer, I'll assume that in the first equation, 'x' is multiplying 3/5 and not just 5.
There are two equations and two unknowns. Since the two equations are linearly independent, you will have an answer. All you have to do is substitute y = 8x in the first equation; we get 8x = -3/5x + 7. Now we want 'x' on the left side; summing both sides of the equation by +(3/5)x, we have 8x + (3/5)x = 7. To add 8 to 3/5, we need to convert 8 to a fraction with 5 in the denominator; that would be 40/5. 40/5 + 3/5 = 43/5. Multiplying both sides by 5/43, we get x = 35/43. Once you have 'x', just substitute it in the second equation, y = 8*35/43 = 6.511 (I used a calculator for this last one).
2007-01-14 13:10:01
·
answer #2
·
answered by ttfreitas 2
·
0⤊
0⤋
y=-3/5x+7 and y=8x
you can either eliminate or substitute... substitute is a little easier in this case
substitute y=8x into y=-3/5x+7
8x=-3/5+7
43/5x=7
multiply each side by 5/43
that will make it
x=78/5
2007-01-14 13:04:52
·
answer #3
·
answered by Amanda 5
·
0⤊
0⤋
y=-3/5x+7
y=8x
8x= - 3/5x + 7
8(3/5x) = 7
24 7
--- =
5x
24= 35x
24/35 =x
-------------------
to find y:
24/35 * 8 = 192/35
2007-01-14 12:57:04
·
answer #4
·
answered by Chocolate Strawberries. 4
·
0⤊
0⤋
plug the y=8x into the other one and solve from there and when you get what y equals plug it back in and solve for x. but dont take my word for it.
2007-01-14 12:53:31
·
answer #5
·
answered by Ky_bello 3
·
0⤊
1⤋
I am not going to spend a huge amount of time on this, since it is the weekend so if you don't understand, ask your teacher (or your kids if you are older)
2007-01-14 12:52:14
·
answer #6
·
answered by burning_glory45 5
·
0⤊
2⤋